Traditional institution for enhancing the sustainability of irrigation management in West Sumatra Indonesia - Ifdal Ifdal; Ami Sukma Utami (Universitas Andalas, 2023)
Indigenous institutions that have been existing within the community for hundreds of years ago can contribute to effective natural resources management, especially by encouraging farmers' participation in irrigation activities. However, due to a new institution introduced by the Indonesian government, such as the water users' Associations (